Assessing the Impact of Institutional Risk Management on Crop Productivity: Investigating the Moderating Influence of Human Resource Risk Management Practices - Hewlett , Dexter Senanu Kofi; Essel-Mensah , Kojo A.; Tee, Evans; Boadi, Lawrence Asare; Sampson, Vivian Esumanba (International Journal of Economics and Financial Issues, 2026)
This study examines the impact of institutional risk management (IRM) and human resource risk management (HRRM) on crop production (CP) in the agricultural sector. This study aimed to investigate the direct impacts of IRM and HRRM on CP, as well as to evaluate the moderating role of IRM in the HRRM-CP relationship. A quantitative research design was utilised, employing structural equation modelling (SEM) to analyse data from agricultural stakeholders. The findings indicate that both IRM and HRRM significantly positively influence CP, suggesting that enhancements in risk management practices can improve agricultural productivity. A 1% increase in HRRM results in a significant rise in CP, and IRM similarly exhibits a positive effect on crop production. When IRM was introduced as an interaction term, its moderating effect on the HRRM-CP relationship was statistically insignificant. This indicates that although both IRM and HRRM independently affect crop production, IRM does not significantly impact the strength of the HRRM-CP relationship. This study presents original findings indicating that HRRM and IRM are essential, yet distinct, factors affecting agricultural outcomes. The findings highlight the necessity for agricultural policymakers and stakeholders to prioritise HRRM and IRM within their risk management frameworks. This approach can promote increased crop yield and support sustainable agricultural advancement.